Proposta pedagógica de tempo integral na educação infantil: análise de uma realidade - CORRÊA, Talita Ananda (Universidade Federal do Oeste do Pará, 2023)
The present research, with a qualitative approach, aimed to analyze the pedagogical proposal of a public institution of Early Childhood Education, in the municipality of Santarém - Pará, seeking to identify the specificities of the full time day job offer. It was based on analysis of the Cultural-Historical Theory of Human Development, through the studies of Vigotski (1993, 1995, 2008) and his collaborators. The methodology used consisted of documentary analysis, observation of two pre-school classes, one full-time and one part-time and a semi-structured interview with the pedagogical coordinator. The results of the study demonstrate that the pedagogical proposal of the institution presents few differences between the days that offer. In the classes, it was noticed that the time spent in the children's care could be better exploited by less repetitive activities, so that the most elaborate knowledge of human production could be explored, such as music , Dance, the plastic arts, literature, among others that help to develop higher psychic functions. The curriculum is based on commemorative dates and activities of seizure of letters and numbers that do not have communicative function for the children. It was also verified that the divergences found in the two classes are related to the physical care of the children, and the activities of play and teaching are "doubled" for those who remain all day in the institution. The communication between full-time teachers occurs in the exchange of schedules, at which point the teacher who will stay the rest of the day with the class arrives and enters the activity of sleep, and the other teacher retires. However, it is only in pedagogical meetings that they talk to plan their practices and check on the activities they are developing. The coordination, together with the UMEI pedagogue, is that they are responsible for the organization of pedagogic meetings, formations and evaluation meetings, teachers and family members attended. Thus, the proposal is effective in an adult-centric perspective for children who are practically oblivious to what is being proposed to them. And since there is no challenge and motivation in the routine, some children try in their own way to resist what is imposed upon them, interacting with them when they are told to wait, communicating when asked to silence and inventing ways to sweeten their childhood. Thus, from the way the full-time and even partial proposal is configured for pre-school classes, it is possible to infer that there are few positive contributions to the humanization process of children. Considering the pedagogical proposal an important tool to guide the practice in the institution, it is necessary that its effectiveness is better instituted by professionals who are part of the education process of small children.